A review of vilazodone exposures with focus on serotonin syndrome effects. (21st October 2017) - Heise, C. William; Malashock, Hannah; Brooks, Daniel E.
Abstract: Background: Vilazodone is an antidepressant with selective serotonin reuptake inhibition and partial 5HT1A agonism. Serotonin syndrome is believed to be due to excessive stimulation of 5-HT2A and 5-HT1A receptors, resulting in the clinical triad of altered mentation, autonomic instability and neuromuscular abnormalities. The goal of this study is to define serotonergic effects after vilazodone exposure. Methods: A retrospective review of two databases: the American Association of Poison Controls Centers' National Poison Data System (NPDS) and the American College of Medical Toxicology's Toxicology Investigators Consortium (ToxIC Registry). A case series of four patients from one medical toxicology service is also presented. Results: During the 52-month study period, a total of 3192 vilazodone human exposures were reported to NPDS. Of these, 1734 (54%) were isolated vilazodone cases. The clinical effects of vilazodone toxicity included drowsiness (20%), vomiting (14%), tachycardia (11%) and agitation (10%). Most patients (71%) had symptoms for between 2 and 24 h, though some (14%) remained symptomatic for more than 24 h. The most common treatment was intravenous fluids (15%) and the most serious intubation (2%). From the ToxIC Registry, a total of 23 cases of vilazodone exposures were identified. Of these, 17 (74%) had vilazodone listed as the first (primary) agent and 10 (43%) involved vilazodone-only ingestions. Nine (39%) cases documented serotonin syndrome; and most (8/9; 89%) listed vilazodone as the primary agent. All ( n  = 4) subjects in the case series with acute vilazodone toxicity had serotonin syndrome. Conclusions: Vilazodone overdose, including vilazodone-only ingestions, are associated with serotonin syndrome. Serotonergic toxicity and appropriate treatments should be considered when caring for patients with vilazodone ingestions.